TREADING TURBULENT WATERS: PAKISTAN’S READINESS TO THE LOOMING THREAT OF MARITIME TERRORISM (Margalla Papers, 2024)
Houthis’ recent attacks on Merchant ships in the Red Sea have renewed focus on maritime terrorism. These attacks have pushed the global power centres to think seriously about this intensifying threat to international maritime trade and movement. South Asia, particularly India and Pakistan, have already faced the issue of marine terrorism, yet it has remained primarily a neglected field of enquiry, particularly in Pakistan. This paper aims to fill this void in the literature by critically analysing the threat of Maritime terrorism to Pakistan and how prepared it is to counter this problem. This paper attempts to dissect the threats that exist in the Arabian Sea and how maritime terrorism has the potential to push Pakistan and India into a new conflict, which may have grave consequences for the global community. The paper starts with an overview of maritime terrorism and how it has evolved over time and with technological advancements. This follows an analysis of marine terrorism incidents in India and Pakistan and how Pakistan has built up its organisational structure to cover the threats posed by it. It contends that Pakistan has a ready organisational structure; it requires improved inter-departmental coordination and more importantly, constitutional cover. In the end, the paper provides policy recommendations at the organisational, national and regional levels to address the issue of maritime terrorism. Bibliography EntryShahid, Mubashar Hassan and Rizwan Zeb. 2024. "Treading Turbulent Waters: Pakistan’s Readiness to the Looming Threat of Maritime Terrorism." Margalla Papers 28 (1): 211-225.